Corporate Diversification and Firm Performance: Evidence from the Nigerian Banking Sector - Okpoa, Asemota Georgina; Eseosa Damiana, Ogedengbe (Journal of Technology Management and Business, 2023)
Corporate diversification plays an important role in strategic decision-making, especially when it comes to corporate expansion and growth. This study examined the impact of corporate diversification on the financial performance of deposit money banks listed on the Nigerian Stock Exchange. The study covered a ten-year period, from 2010 to 2019, and included data from the annual reports of thirteen listed deposit-taking institutions. Two accounting and one economic measure of firm performance were chosen as indices for the response variables, while the predictor variables were specialisation, related diversification, unrelated diversification and cross-border diversification. Using the panel generalised least square method, the study found that specialisation and related diversification significantly influence firm performance in the Nigerian banking sector. The study, therefore, recommends cross-border geographical expansion for deposit banks in Nigeria while maintaining services in areas of expertise.